Multi-objective optimization of the multi-story residential building with passive design strategy in South Korea. (October 2021) - Jung, Yujun; Heo, Yeonsook; Lee, Hoseong
Abstract: In this study, the multi-objective optimization of passive design strategy was conducted for multi-story residential buildings in South Korea. The performance of passive design was analyzed in terms of energy, environmental, and economic metrics, considering the life cycle performance. Various passive design factors were considered to better reflect the actual phenomenon, and a novel simulation modeling method which includes building model simplification and meta model was developed for an accurate and fast calculation of optimization. The sensitivity analysis was conducted to decide critical design factors in optimization and showed that the most influential design factors are airtightness, occupants, and window-to-wall ratio. Throughout optimization, the energy, environmental impact, and economic feasibility in multi-story residential building can be improved by 52.7%, 39.5%, and 36.9%, respectively. The uncertainty of optimal solution was analyzed though the uncertainty analysis. If the utility cost increases and energy system efficiency improves in the future, the optimal passive design solution will not change significantly in energy and economic feasibility, however it may become more critical in the environmental impact. Highlights: Optimization of passive design strategy is conducted for residential buildings. A novel method includes building model simplification and meta model development. The proposed method is developed for accurate and fast calculation of optimization. Life cycle based multi-criteria evaluation of building performance is conducted.